Discussion on Islamic Finance and Small Medium Enterprises’ Financial Accessibility - Mohd Thas Thaker, Hassanudin; Sakaran, Kanan Chandra (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2019)
This study attempts to provide some understanding of SMEs’ access to f inance in Malaysia using Islamic finance and its successfulness. The innovation that taking place in the Malaysia financial landscape has benefits the SMEs in accessing f inancial assistance without relying on the traditional mode of financing. The role of government of Malaysia is also undisputable in supporting the progression of SMEs via various policy implementation. Apparently, in the context of Indonesia, the role SMEs is also undeniable in boosting up the growth of Indonesian economy. Statistically speaking, SMEs in Indonesia represent about 99 percent in all economic sector and involved labor participation of almost 95 percent. Although the contributions are wider, the issue of financial accessibility still becomes one of the main hurdles that block the development of SMEs in Indonesia. Therefore, the present study has used content analysis to critically look at the success of SMEs financing in Malaysia based on Islamic financing provides some recommendations based on Malaysian SMEs f inancing successfulness for Indonesian authority to further restructure and enhance their existing financial assistance to the SMEs based on Islamic financing.Abstrak:Studi membahas tentang akses Usaha Kecil Menengah terhadap pembiayaan keuangan Islam di Malaysia dan keberhasilannya. Inovasi dalam pembiayaan lanskap di Malaysia memberikan manfaat terhadap UKM di negara tersebut dalam mengakses bantuan pembiayaan tanpa harus mengandalkan moda pembiayaan tradisional. Peran pemerintah Malaysia juga tidak dapat dipungkiri dalam upaya mendukung perkembangan UKM melalui berbagai kebijakan. Dalam konteks Indonesia, peran UKM dalam mendongkrak perkembangan ekonomi Indonesia pun tidak dapat dibantah. Secara statistik, UKM di Indonesia mewakili sekitar 99 persen di seluruh sektor ekonomi, serta melibatkan partisipasi pekerja hampir 95 persen. Meskipun memiliki kontribusi yang lebih luas, akses terhadap pembiayaan masih menjadi salah satu kendala utama yang menghambat perkembangan UKM di Indonesia. Untuk itu, penelitian ini mengkaji secara kritis keberhasilan UKM Malaysia yang menggunakan pembiayaan Islam, untuk kemudian menjadi rekomendasi bagi pihak yang berwenang di Indonesia dalam upaya rekonstruksi dan peningkatan bantuan pembiayaan bagi UKM berdasarkan mekanisme pembiayaan syariah.